Oxidative stress in major thermal burns: Its implications and significance - Ranjith James Babu; Mary Babu (Wolters Kluwer Medknow Publications, 2018)
Introduction: Thermal burns could prove dreadful to humankind. The morbidity and mortality is the interplay of intraneous and extraneous factors. Multidisciplinary approach plays a cardinal role in managing this catastrophe. This study is carried out to analyze the oxidative stress in thermal burns, its implications in management, and the significance it carries with it. Materials and Methods: This prospective study was carried out in 30 patients from January 2016 to December 2016. Quantitative analysis of oxidative stress and total antioxidant capacity was done on postburn day 3 and every 5 days thereafter. Results: The quantitative oxidative stress level was high, and antioxidant capacity was low in patients who had higher percentage total body surface area burn and predominant deep burn with temporal analysis. The patterns were strikingly different in patients who had mortality with patients who survived. Discussion: Thermal burn releases reactive oxygen species which causes profound changes in internal and external milieu. This alters the physiological response to treatment and impresses on the morbidity and mortality of the patient. Conclusion: Thereby, it could be construed that oxidative stress along with tailored intervention, timing of treatment, and recalcitrant attitude to treatment methodology has a significant role in determining the outcome of burn patients.